The Cambridge handbook of facial recognition in the modern state - Matulionytė, Rita; Zalnieriute, Monika (Cambridge University Press, 2024)
In situations ranging from border control to policing and welfare, governments are using automated facial recognition technology (FRT) to collect taxes, prevent crime, police cities and control immigration. FRT involves the processing of a person's facial image, usually for identification, categorisation or counting. This ambitious handbook brings together a diverse group of legal, computer, communications, and social and political science scholars to shed light on how FRT has been developed, used by public authorities, and regulated in different jurisdictions across five continents. Informed by their experiences working on FRT across the globe, chapter authors analyse the increasing deployment of FRT in public and private life. The collection argues for the passage of new laws, rules, frameworks, and approaches to prevent harms of FRT in the modern state and advances the debate on scrutiny of power and accountability of public authorities which use FRT. This book is also available as Open Access on Cambridge Core